Anterior Pedicled Lateral Nasal Wall Flap for Endonasal Lining: A Radiologic and Anatomical Study. (3rd November 2020) - Langdon, Cristóbal; Yuen‐Ato, Kathy; Pereira‐Perez, Carla; Arancibia, Claudio; Alobid, Isam
Abstract : Objectives/Hypothesis: The objective of this radiological/anatomical study was to evaluate the feasibility of a new endoscopic technique that uses the anterior pedicled lateral nasal flap (APLNW) for the endonasal lining in complex nasal reconstructions. Study Design: An anatomical study was performed on 20 nasal fossae of cadaverous specimens to measure the area and lengths of the anterior pedicled nasal lateral wall flap. In addition, a radiological analysis with computed tomography was performed in 150 nostrils to determine the potential donor of the simple and extended flap in the nasal fossa floor. Complex nasal reconstruction with nasofrontal flap and internal lining using the lateral wall pedicled flap was performed in 3 patients. Results: Complete reconstruction for the inner lining of the nasal tip and lateral nasal wall was achieved in the cadaveric study (10 specimens). The surface areas of the simple and extended APLNW flaps were 7.53 (standard deviation [SD] 1.25) cm 2 and 24.6 (SD 3.14) cm 2, respectively. Using computed tomography scans, we determined that to reconstruct defects secondary to full‐thickness nasal defects, the APLNW flap surface for the simple and extended versions was 7.90 (SD 1.68) cm 2 and 23.64 (SD 4.7) cm 2 . We present one case were the APLNW flap was used. Conclusions: The simple or expanded APLNW flap represents a feasible option to reconstruct the internal lining in complex nasal reconstruction. Level of Evidence: NA Laryngoscope, 131:E1462–E1467, 2021